The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2958.2005.05005.x
|View full text |Cite
|
Sign up to set email alerts
|

An exonuclease I‐sensitive DNA repair pathway in Deinococcus radiodurans: a major determinant of radiation resistance

Abstract: SummaryDeinococcus radiodurans R1 recovering from acute dose of γ γ γ γ radiation shows a biphasic mechanism of DNA double-strand break repair. The possible involvement of microsequence homology-dependent, or nonhomologous end joining type mechanisms during initial period followed by RecA-dependent homologous recombination pathways has been suggested for the reconstruction of complete genomes in this microbe. We have exploited the known roles of exo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 38 publications
(55 reference statements)
1
67
0
Order By: Relevance
“…This pathway is inhibited by the SbcB nuclease (reference 24 and references therein), and D. radiodurans is naturally devoid of the SbcB protein. Moreover, it was shown that expression in trans of the SbcB protein from E. coli renders D. radiodurans cells radiation sensitive (35). Thus, a RecF-like pathway may operate in D. radiodurans to generate 3Ј overhangs of single-stranded DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is inhibited by the SbcB nuclease (reference 24 and references therein), and D. radiodurans is naturally devoid of the SbcB protein. Moreover, it was shown that expression in trans of the SbcB protein from E. coli renders D. radiodurans cells radiation sensitive (35). Thus, a RecF-like pathway may operate in D. radiodurans to generate 3Ј overhangs of single-stranded DNA.…”
Section: Discussionmentioning
confidence: 99%
“…6, step 2). The 5Ј-to-3Ј polarity of end recession in D. radiodurans was indirectly demonstrated by expression in trans of the SbcB 3Ј-5Ј exonuclease from E. coli, which rendered D. radiodurans radiation sensitive and inhibited DNA double-strand-break repair (418). Among possible candidates for 5Ј-3Ј exonuclease activity in D. radiodurans are RecJ and the 5Ј-3Ј exonuclease activity of Pol I.…”
Section: Dna Degradation In Irradiated D Radioduransmentioning
confidence: 99%
“…D. radiodurans does not encode RecB and RecC homologs, or SbcB (a 3Ј-5Ј ssDNA nuclease), and the levels of nuclease activity in deinococcal cell extracts are consequently much lower than that in E. coli extracts (288). The overexpression of E. coli RecBC (288) and SbcB (418) in D. radiodurans sensitizes the cells to ionizing radiation and delays or inhibits DSB repair in gamma-irradiated cells, respectively. RecBC-expressing D. radiodurans cells suffer from an extensive degradation of DNA ends, while the inhibition of DSB repair in SbcB-expressing cells suggests that 3Ј ssDNA ends are indispensable for the recombinational repair of DSBs (418).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGY agar plates containing D. radiodurans R1 and its derivatives were incubated at 32°C for 48 h before the colonies were counted. The shuttle expression vector pRADgro and derivatives of this vector were maintained in E. coli strain HB101 as described previously (34). Other recombinant techniques used have been described previously (37).…”
Section: Methodsmentioning
confidence: 99%